Treasure hunt for kids over 500 hidden pictures to search for, sort and count - Gaughan,Rhea (New York, Created for St. Martin's Press by Priddy Books, 2019)
Eager young treasure hunters can develop counting and sorting skills as they search for the hundreds of hidden things in this bright, engaging seek-and-find book. The fun and colorful scenes include a beach, jungle, farm, pirates, space, princesses and dinosaurs!
Keywords: Picture book suitable for 3+